Are experts’ noticing focuses regarding the learning potential of tasks and its use consistent across instructional situations? A secondary analysis - Paul, Josephine F.; Dreher, Anika; Wang, Ting-Ying; Hsieh, Feng-Jui; Hansen, Linn; Lindmeier, Anke (Proceedings of the 46th Conference of the International Group for the Psychology of Mathematics Education, 2023)
Professional noticing is an important aspect of teacher expertise. Research has shown that noticing might vary between cultures. Prior studies indicate that culture-specific norms influence noticing. But, these findings stem from group comparisons. The reported study aims at understanding how individual focuses may influence noticing in addition to cultural influences. It uses noticing vignettes to investigate the aspects Western (German, N=17) and East Asian (Taiwanese, N=19) professors in mathematics education (experts) focus their attention on when evaluating the potential of tasks for mathematical learning and its use in instruction. We present preliminary results regarding the consistency of the focuses across situations, identify five types of experts regarding their focuses, and discuss implications for further noticing research.
CRIS-Team Scopus Importer:2024-10-02